Autostereoscopic displays in computer assisted surgery - Gümüş, Caner. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2010., 2010)
Using images for diagnosis, therapy and surgery is a widely used option as evidenced by many articles in the literature. In conventional systems standard two-dimensional (2D) displays are used to view the images even though the images are three-dimensional (3D) reconstructed. In this study, we used a computerized surgical assistant whose core functionalities are provided by an open source software package called Slicer. Slicer uniquely integrates several facets of image quided therapy into a single environment and has capabilities for visualization, surgical planning and guidance. We performed basic tasks of computer assisted surgery such as registration, segmentation, surface model generation and 3D visualization on medical images and displayed the reconstructed images on an autostereoscopic display so that the images with depth can be viewed without the need to wear any special eyeglasses or headgear.|Keywords: Autostereoscopic displays, Slicer, Visualization, Computer Assisted Surgery.
Keywords: Computer-assisted surgery.